Trends in One Month and One Year Hemorrhagic Stroke Case Fatality Rates in the Czech Republic between 1998 and 2015 - Bryndziar, Tomas; Sedova, Petra; Brown, Robert D; Fiserova, Eva; Zvolsky, Miroslav; Bednarik, Josef; Mikulik, Robert (Journal of stroke and cerebrovascular diseases, 2020)
BACKGROUND: This retrospective cross-sectional study reports 1 month and 1 year intracerebral hemorrhage (ICH) and subarachnoid hemorrhage (SAH) case fatality rates and their temporal trends in the Czech Republic between 1998 and 2015. METHODS: Utilizing the National Register of Hospitalized Patients, we randomly selected 600 patients hospitalized for ICH and 600 patients hospitalized for SAH for each year from 1998 to 2015, and identified those who died, regardless of cause, using the Czech National Mortality Registry. We calculated crude and age-adjusted 1 month and 1 year case fatality rates for ICH and SAH. Long-term trends of the crude rates were analyzed using a one-sided Cochran Armitage test. RESULTS: A total of 21,600 cases hospitalized for SAH and ICH (10,800 for each) between 1998 and 2015 were randomly selected for analysis. One month case fatality of SAH overall and in women has decreased by 0.2% (P = .006) and 0.3% per year (P = .04), respectively. Overall 1 year case fatality of SAH has decreased by 0.2% per year (P = .03). One month case fatality rate of ICH overall and in men has decreased by 0.2% (p=0.01) and 0.4% (P = .0007), respectively. One year case fatality of ICH in men has decreased by 0.2% per year (P = .047). CONCLUSIONS: One month and 1 year case fatality rates for SAH and ICH have been decreasing in the Czech Republic between 1998 and 2015, and are similar or lower than those reported from other developed European countries.
Keywords: subarachnoid hemorrhage; senioři; Cross-Sectional Studies; Stroke; Sex Distribution; Retrospective Studies; Time Factors; Česká republika; Middle Aged; registrace; mužské pohlaví; Intracerebral hemorrhage; subarachnoidální krvácení; příčina smrti; průřezové studie; Adult; Czech Republic; Registries; cévní mozková příhoda; mortalita v nemocnicích; cerebrální krvácení; ženské pohlaví; retrospektivní studie; Humans; case fatality; časové faktory; lidé středního věku; Hospital Mortality; Cerebral Hemorrhage; Subarachnoid Hemorrhage; trends; Hospitalization; hospitalizace; dospělí; rozložení podle pohlaví; Female; Aged; Cause of Death; lidé; Male